Analisis Faktor-Faktor Yang Mempengaruhi Akuntabilitas Pengelolaan Keuangan Desa Terhadap Aparatur Desa - Setiawan, Ade Budi; Kusuma , I.C.; Hambani , S; Agustin , Indah (Jurnal Akunida, 2022)
Accountability Village Financial Management Accountability is an obligation with the principle that every village financial management activity must be accountable to the community in accordance with applicable laws and explain the performance or actions of the village head, village financial reports that have been processed in their books and then submitted to the Regent. The population in this study The sample is 100 respondents from village government officials who are in 20 village offices who are responsible for and understand village financial management. and data analysis and hypothesis testing were carried out using descriptive statistics with classical assumption tests and multiple linear regression using the JASPprogram. The results of this study simultaneously the competence of government officials, information technology, transparency, supervision, community participation have a significant effect on the accountability of village fund management.